RESTRUKTURISASI KREDIT KENDARAAN BERMOTOR PERUSAHAAN PEMBIAYAAN AKIBAT SITUASI PANDEMIC COVID-19 - Marta Saputra, Fadhli; Faniyah, Iyah (UNES Law Review, 2021)
With the increase and spread of the number of cases of Corona Virus Disease 2019 (Covid-19), the impact of increasing the percentage of non-performing loans at PT. Adira Dinamika Multi Finance, Tbk Padang Branch, from the data obtained from bad loans before the Covid-19 Pandemic there were around 500 (five hundred). Restructuring of Motor Vehicle Loans for Financing Companies Due to the Covid-19 Pendemic Situation at PT. Adira Dinamika Multi Finance, Tbk Padang Branch is implemented in the form of rescheduled installment payments and there are consumers (creditors) who have been given restructuring with terms and conditions agreed by both parties, provided that the debtor or customer who submitted it is affected by Covid 19, the collateral or product being credited is still with the debtor, it is not transferred or over credited to another party, the financing value (principal debt) is below Rp10 billion. Preventive supervision of the Financial Services Authority (OJK) in the West Sumatra Region OJK will send a letter of warning to Financing Companies that do not carry out restructuring programs during the current COVID-19 pandemic, and repressively to Financing Companies that do not implement Restructuring programs as per government policy. OJK will impose administrative sanctions in the form of fines to financing companies.